The Effect of Village Financial Report Presentation and Individual Morality on Fraud Prevention in Village Fund Management - Mawikere, Lidia; Loupatty, Rivanda Injil Gabriel (Kompartemen : Jurnal Ilmiah Akuntansi, 2025)
This study aims to examine the effect of the presentation of village financial reports and individual morality on fraud prevention. This study uses a quantitative method. The population used in this study were the Village Head, Village Secretary, Village Treasurer, and Village Consultative Body (BPD) users of village financial reports in West Kawangkoan District, Minahasa Regency. The sampling technique used census sampling or total sampling. The data collection method used was the questionnaire method. The data analysis technique used was multiple linear regression. These results indicate that the presentation of village financial reports and individual morality have a positive effect on fraud prevention in village fund management.